Engineered bacteriorhodopsin: a molecular scale potential switch. - Patil, A; Premaraban, T; Berthoumieu, O; Watts, A; Davis, J (2012)
Bacteriorhodopsin, BR, is a natural, photoresponsive, biomolecule that has potential application in data storage, imaging and sensing. Being membrane-bound, however, it is coupled with metallic electronic surfaces only with some difficulty. We report herein a facile method to generate uniformly orientated, anchored and active monolayers of BR on metallic electrodes. In the present study, the cytoplasmic side of the BR is equipped with an engineered cysteine to achieve largely lipid-free, orientation-specific, highly stable, covalent immobilization on gold surfaces. By using non-invasive Kelvin probe force microscopy, it is possible to measure the light-induced proton accumulation at the extracellular protein surface at truly molecular scales. The intimate probe-BR interaction possible on lipid removal facilitates the detection of photoinduced surface potential switching substantially larger ((20.4 ± 7.5) mV) with functional single delipidated mutant BR trimers than for the wild-type protein. The proton pumping detected is also notably highly unidirectional with the orientated protein.